The effect of desiccation on water sorption, solubility and hygroscopic volumetric expansion of dentine replacement materials. Issue 8 (August 2018) - Mustafa, Ruba; Alshali, Ruwaida Z.; Silikas, Nick
Abstract: Objective: To evaluate water sorption, solubility and hygroscopic expansion and the effect of desiccation for a calcium silicate-based material, a conventional glass ionomer, and a resin-modified glass ionomer. Methods: Water sorption, solubility and hygroscopic expansion of Biodentine™ (BD), GC Fuji IX GP ® FAST (FJ), and Ionolux (IO) were tested under two pre-storage conditions: with desiccation and without desiccation. Disc-shaped samples (n = 5) were immersed in water and weighed at different time intervals (1 h, 24 h, 3 d, 7 d and 30 d) and hygroscopic expansion was recorded at 7 d and 30 d. Data were analysed using Factorial repeated measures ANOVA, one-way/two-way ANOVA, Independent samples t -test and Tukey's post hoc test ( α  = 0.05). Results: With desiccation, sorption of IO and FJ was 124.33 μg/mm 3 and 79.97 μg/mm 3 respectively. Solubility was −12.36 μg/mm 3 for IO and −20.19 μg/mm 3 for FJ. Hygroscopic expansion was 3.01% for IO and −2.35% for FJ. Without desiccation, sorption was in the order: IO ˃ BD ˃ FJ (130.35 μg/mm 3, 122.07 μg/mm 3, and 107.21 μg/mm 3 respectively), while solubility order was: BD ˃ FJ ˃ IO (154.83 μg/mm 3, 88.82 μg/mm 3, and 25.67 μg/mm 3 respectively). IO and FJ showed significant difference in sorption and solubility between the two pre-storage treatment groups (p ˂ 0.005). Hygroscopic expansion was in the order: IO ˃ BD ˃ FJ. Significance: BD had the highest solubility while IO had the least. The relatively stable polymeric resin in IO may contribute to its low solubility but high hygroscopic expansion. Desiccation had significant effect on sorption, solubility and volumetric expansion of water-based materials.